Визначення тривалості підсушування ковбасних виробів - Петриченко, Сергій Володимирович; Петриченко, Сергей Владимирович; Petrychenko, Serhii; Олексієнко, Вадим Олександрович; Алексеенко, Вадим Александрович; Oleksiienko, Vadym (Мелітополь: ТДАТУ, 2019)
UK: В статті наведено результати аналізу процесів термічної обробки ковбасних виробів та теоретичні передумови визначення тривалості процесу підсушування варених ковбас з метою забезпечення високої якості продукції при мінімальних витратах енергоносіїв. RU: В статье приведены результаты анализа процессов термической обработки колбасных изделий и теоретические предпосылки определения продолжительности процесса подсушки вареных колбас с целью обеспечения высокого качества продукции при минимальных затратах энергоносителей. EN: The traditional technology provides for the heat treatment of cooked sausages in three stages: drying, roasting and cooking, which differ in the modes of the heating medium. All three processes of heat treatment consist in the redistribution of heat supplied to the product from the heating medium. Meat products are objects with a rather complex structure. Therefore, to take it into account when calculating the processes of distribution of heat and matter is difficult and practically hardly expedient. During heat treatment of meat products, the transfer of mass and energy occurs due to the thermal motion of the micro particles. Mass transfer is carried out through diffusion processes. During diffusion, as a result of the thermal motion of particles of a substance, the mutual penetration of particles of the contacting bodies occurs. Diffusion ultimately leads to a leveling out of concentration. The transfer of heat energy occurs due to heat conduction. Heat is transferred from warmer to less heated parts of the body. The process of energy and mass transfer is possible only in the presence of a driving force, i.e. when the system deviates from the equilibrium state. The article presents the results of the analysis of the processes of heat treatment of sausages and theoretical prerequisites for determining the duration of the process of drying cooked sausages in order to ensure high quality products with minimal energy costs. The results obtained can be used both in the educational process and in scientific research.
Определение продолжительности подсушки колбасных изделий
Determination of the delay duration sausage products
Keywords: ковбасні вироби; термічна обробка; підсушування; тривалість; температуропровідність; фронт збурення